A design process for the adoption of composite materials and supply chain reconfiguration supported by a software tool. (July 2018) - Coronado Mondragon, Adrian E.; Coronado Mondragon, Christian E.; Hogg, Paul J.; Rodríguez-López, Nuria
Highlights: Composite materials adoption may alter the structure of the supply chain. The proposed approach may address the lack of evaluation tools for using composites. The developed tool can generate a graphical representation of a bill of materials. The developed tool facilitates the substitution of sub-assemblies with composites. Abstract: Composite materials comprising fiber reinforced polymers (FRPs) possess advantageous properties that surpass that of traditional materials. The use of composite materials may give the opportunity to improve the technical specifications of a manufactured module and also impact the configuration of the supply chain. However, this represents a challenging decision-making process as various technologies are available for the manufacturing of composite materials. This paper proposes a design process based on the identification of the bill of materials of a component where the substitution of certain sub-assemblies using composite materials may result in the reduction of parts, operations and suppliers. The design process is supported by a customized software tool that generates a graphic representation of the bill of materials of the selected module, allowing users to choose a specific sub-assembly, select composite materials process types and identify potential suppliers from a database. An industry case involving the production of a module used in urban buses/long distance coach manufacturing is employed to illustrate the proposed design process. The software tool developed satisfactorily integrates the bill-of-materials and current product and process specifications with an existing costing engine and a populated database of potential composite materials suppliers. The approach presented in the paper can be used to address the lack of evaluation tools for using composite materials/carbon fiber.